What's new Scooby-Doo? [videorecording (DVD)] The complete third season - Kasem, Casey; Welker, Frank; Cohn, Mindy, 1966- (Warner Home Video, 2008)
Everyone's favorite crime solvers keep their cool in any arena from a wrestling match gone wrong to a haunted stock car race, even a mini golf tournament terrorized by a metallic clown. The gang also visits Paris, Moscow, Hong Kong, and Australia.